Simultaneous acute Marchiafava–Bignami disease and central pontine myelinolysis: A case report of a challenging diagnosis. Issue 8 (February 2018) - Tsai, Chun-Yi; Huang, Po-Kai; Huang, Poyin
Abstract: Rationale: Marchiafava–Bignami disease (MBD) is a rare disease characterized by demyelination of the corpus callosum. It is most commonly seen in patients with chronic alcoholism. The clinical diagnosis of MBD can be difficult due to its nonspecific manifestation. Central pontine myelinolysis (CPM) occurs mostly as a complication of severe and prolonged hyponatremia, especially when corrected too rapidly. However, CPM can be associated with chronic alcoholism and its clinical presentation can be heterogeneous. Because both MBD and CPM can have fatal outcomes, early recognition and treatment can result in a better prognosis. We present a very rare case of simultaneous acute Marchiafava–Bignami disease and central pontine myelinolysis in a patient with chronic alcoholism who was diagnosed unexpectedly using brain magnetic resonance imaging and improved after proper treatment. Patient concerns: We presented a case of a 39-year-old patient who visited the hospital with general weakness and an altered neurologic condition after a week of vomiting. Diagnosis: The patient was diagnosed with simultaneous acute Marchiafava–Bignami disease and central pontine myelinolysis using brain magnetic resonance imaging. Intervention: Administration of a high dose of thiamine. Outcomes: The neurologic signs improved after a week of thiamine administration. Lessons: This case suggests that Marchiafava–Bignami disease and central pontine myelinolysis might have a common pathogenesis, and brain magnetic resonance imaging is of crucial importance in chronic alcoholic patients presenting with nonspecific neurological deterioration. The appropriate administration of thiamine may prevent poor outcomes.